PHASE TRANSITIONS AND HEAT CONDUCTION IN POST-GLACIAL REBOUND - Tamisiea M.E.; Wahr J.M. (My University, 2002)
We have developed a method for including phase boundary conditions into post-glacial rebound models that allows for conduction of latent heat away from the boundary. This method returns the chemical boundary results if latent heat conducts away from the phase boundary too slowly to allow the transition to proceed, as is commonly argued. This is not necessarily the case, however. For example, the secular change of the geoid and the vertical uplift rates for phase boundaries with latent heat conduction can differ from the chemical boundary results by up to 10 and 15 per cent, respectively. When modelling the phase transition, we consider two scenarios: the latent heat is released either at a narrow boundary that separates the two phases or over a thick mixed region of the two phases. In the case where the phase transition occurs over a thick enough region (5-10 km), the final results are close to the results obtained by considering a phase boundary that ignores the release of latent heat completely. This thick boundary formulation also suggest that the phase boundaries could respond nearly instantaneously, changing both the elastic load and body Love numbers. However, we have not considered kinetics, the energetics of the mechanisms of the phase transitions, in this formulation. This work suggests a greater knowledge of the kinetics near equilibrium phase transitions is required. A naive calculation indicates that the kinetics will not be a significant factor for post-glacial rebound but will be a limiting factor for earth tides.
Keywords: GLACIAL REBOUND; MANTLE DISCONTINUITIES; PHASE TRANSITIONS; THERMAL CONDUCTIVITY